Status aspirations, wealth inequality, and economic growth - Oded Stark (Institute for Advanced Studies (IHS), 2005)
This paper argues that an increase in the inequality of wealth prompts a stronger quest for status that in turn fosters the accumulation of wealth. It proposes a measure for an individual's want of social status. For a given level of a population's wealth, the corresponding aggregate measure of want of social status is shown to be positively related to the Gini coefficient of wealth inequality. Hence the Gini coefficient and growth are positively correlated, holding the population's wealth constant.
Keywords: A13; A14; D31; D63; O40; 330; quest for status; distribution of wealth; economic growth; Vermögensverteilung; Einkommensverteilung; Sozialer Status; Wirtschaftswachstum; Theorie